DINAMIKA HUKUM DI ERA DIGITAL : TANTANGAN REGULASI TERHADAP AI DAN KEADAAN DATA - Meike Negawati Kesek (EDU RESEARCH, 2025)
The rapid advancement of digital technology, particularly Artificial Intelligence (AI) and data security, has brought significant legal challenges. While AI offers efficiency and innovation, it also raises concerns about individual rights, privacy, and the adequacy of existing regulations. One of the primary issues is the lack of comprehensive legal frameworks that can keep pace with AI's rapid development. Additionally, accountability for AI-driven decisions remains a legal gray area, especially in cases involving bias or errors. Transparency and ethical considerations must be integrated into AI regulations to ensure fairness and responsibility.Data security is another critical concern in the digital era. The increasing risk of cyberattacks and unauthorized data usage necessitates stringent data protection laws. Regulations such as the General Data Protection Regulation (GDPR) in Europe and Indonesia’s Personal Data Protection Law aim to safeguard user data, but enforcement remains a challenge. Furthermore, collaboration between governments and the private sector is essential to create adaptive regulatory frameworks that balance innovation and security. This paper explores the legal dynamics of the digital era by analyzing regulatory challenges related to AI and data security. A flexible and adaptive legal approach is necessary to ensure that technological advancements do not compromise individual rights and security while fostering responsible innovation.